Efficiency of zakat institutions in Malaysia and its determinants - Abd. Wahab, Norazlin; Abdul Rahman, Abdul Rahim (2011)
Zakat is one of the five basic pillars in Islam It is an obligation of Muslims to give a specific amount of their wealth (with certain conditions and requirements) to beneficiaries called al-mustahiqqin with the main objective of the achievement of socioeconomic justice. Zakat institutions are trusted bodies that manage zakat in Muslim countries. In Malaysia, such zakat institutions are State Islamic Religious Councils (SIRCs). The institutions are expected to play a key role in promoting the socio-economic objectives of zakat in Malaysia. Thus, it is of prime importance that these institutions are being managed effectively and efficiently. The purpose of this paper is to analyze the efficiency of zakat institutions in Malaysia. This study uses Data Envelopment Analysis (DEA) method to estimate zakat efficiency and Tobit model to determine the efficiency of zakat institutions in Malaysia. We use three different types of DEA model which are technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) Model. The data consist of a panel of fourteen State Islamic Religious Councils (SIRCs) in Malaysia during the period of 2003 to 2007. Further, Tobit Analysis is utilized in the second stage to determine factors that influence the efficiency of zakat institutions in Malaysia. During the study period, our results suggest that pure technical inefficiency rather than scale inefficiency has resulted in the zakat institutions inefficiency. This could be due to inability of the institutions in using the technology available to collect more zakat collection and distribute it to the recipients. Examination of the return to scale revealed that more than half of zakat institutions in Malaysia were scale inefficient (operating at DRS or IRS). The empirical findings suggest that zakat payment system, computerized zakat system, board size, audit committee and decentralization significantly affect efficiency of zakat institutions in Malaysia.